2022
DOI: 10.1007/s40592-022-00163-7
|View full text |Cite
|
Sign up to set email alerts
|

Public health ethics: critiques of the “new normal”

Abstract: The global response to the recent coronavirus pandemic has revealed an ethical crisis in public health. This article analyses key pandemic public health policies in light of widely accepted ethical principles: the need for evidence, the least restrictive/harmful alternative, proportionality, equity, reciprocity, due legal process, and transparency. Many policies would be considered unacceptable according to pre-pandemic norms of public health ethics. There are thus significant opportunities to develop more eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Our investigation revealed that few COVID-19 public health guidelines considered values and preferences, which may have contributed to unpopular pandemic policies and led to an erosion of trust in public health (35)(36)(37)(38)(74)(75)(76)(77).This erosion of trust may present a challenge for managing future crises, which may again require cohesive and coordinated efforts from the public.…”
Section: Discussionmentioning
confidence: 96%
“…Our investigation revealed that few COVID-19 public health guidelines considered values and preferences, which may have contributed to unpopular pandemic policies and led to an erosion of trust in public health (35)(36)(37)(38)(74)(75)(76)(77).This erosion of trust may present a challenge for managing future crises, which may again require cohesive and coordinated efforts from the public.…”
Section: Discussionmentioning
confidence: 96%
“…Further, it is now well recognised that the harms of stringent public health measures are often concentrated among disadvantaged groups. 41 If the transmission dynamics of Nipah virus were to significantly change toward higher risk of human-to-human spread among casual contacts, wider public health measures may, under certain conditions, become more ethically acceptable. However, such measures are not currently justifable given that most spread of Nipah virus occurs among close contacts, and the previous Kerala outbreak in 2018 was controlled without extreme measures such as lockdown -with the response instead focusing on healthcare settings in particular 22 .…”
Section: Use Of Excessively Stringent Public Health Measuresmentioning
confidence: 99%
“…Substantial mathematical modeling efforts have focused on health and economic impacts of severe acute respiratory syndrome (SARS), pandemic influenza, and coronavirus disease 2019 (COVID- 19), as well as the impacts of public health interventions (7,8). However, although numerous ethical considerations are directly relevant to the justification of epidemic control policies (9,10), investigations of the ethical implications of pandemic response in general and the COVID-19 response in particular have typically focused on allocation of scarce resources (9,(11)(12)(13)(14), disparities in health outcomes (15), and issues of research ethics (16,17), as opposed to quantitatively informed ethical analysis of the benefits and harms of control policies and individual compliance with public health measures. This article examines mathematical modeling techniques that we have developed to explore how individual and collective behavior changes can affect two specific outcomes: (i) the probability that an epidemic becomes established in a population and (ii) the total number of infections that occur once an epidemic is established.…”
Section: Introductionmentioning
confidence: 99%